The Effect of Discipline Motivation and Compensation on Employee Performance at the Office of PT. PLN (Persero) Region I Aceh - Wani, Cut Eva; Jamali; Jamil, Muhammad; Suhaina (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2022)
This study aims to determine the effect of Motivation, Discipline and Compensation on Employee Performance of PT. PLN (Persero) Aceh Region, This research was conducted in the city of Banda Aceh, with a total sample of 144 respondents, where the sampling used as respondents was carried out in the form of a census, namely making the entire population of employees of PT. PLN (Persero) Aceh Region, as respondents. The data analyzed in this study is primary data in the form of questionnaire circulation. The data is then processed through multiple linear regression analysis with the help of SPSS. The objects in this study are the facilities, individual abilities, and efforts of the independent variables. performance. The results of this study identified that simultaneously, the variable Motivation and Compensation on Employee Performance had a significant effect on performance, while partially, the variable Motivation and Discipline also had a significant effect on employee performance at PT. PLN (Persero) Aceh Region.